2009
DOI: 10.1194/jlr.d800040-jlr200
|View full text |Cite
|
Sign up to set email alerts
|

Highly sensitive quantification of key regulatory oxysterols in biological samples by LC-ESI-MS/MS

Abstract: We describe a highly sensitive and specific method for the quantification of key regulatory oxysterols in biological samples. This method is based upon a stable isotope dilution technique by liquid chromatography-tandem mass spectrometry (LC-MS/MS). After alkaline hydrolysis of human serum (5 ml) or rat liver microsomes (1 mg protein), oxysterols were extracted, derivatized into picolinyl esters, and analyzed by LC-MS/MS using the electrospray ionization mode. The detection limits of the picolinyl esters of 4b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
157
2

Year Published

2010
2010
2023
2023

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 177 publications
(159 citation statements)
references
References 34 publications
0
157
2
Order By: Relevance
“…Thus the magnitude of change in CYP3A activity in ESRD patients is not clear. However, CYP3A activity in patients in this study appeared to be lower compared with Japanese healthy volunteers reported previously (77.0 ± 40.0 ng ml À1 ) [34]. Second, it remains uncertain whether CYP3A5 activity actually decreases in renal failure.…”
Section: Discussioncontrasting
confidence: 49%
“…Thus the magnitude of change in CYP3A activity in ESRD patients is not clear. However, CYP3A activity in patients in this study appeared to be lower compared with Japanese healthy volunteers reported previously (77.0 ± 40.0 ng ml À1 ) [34]. Second, it remains uncertain whether CYP3A5 activity actually decreases in renal failure.…”
Section: Discussioncontrasting
confidence: 49%
“…The linearity of free cholesterol was between 3.9 µg/mL and 250 µg/mL while that of total cholesterol was between 15.6 µg/mL and 1.0 mg/mL. The levels of 7α-HC in serum were measured using the liquid chromatography mass spectrometry (LC-MS) method according to a previously described method [13] with minor modifications. Briefly, 200 µL of serum was saponified in 0.5 mL of 1 mol/L ethanolic NaOH for 1 h at 37 °C in a shaking water bath.…”
Section: Animal Experimentsmentioning
confidence: 99%
“…The concentrations in serum of sitosterol, campesterol and lathosterol were measured by liquid chromatography-tandem mass spectrometry (LC-MS/ MS) as described elsewhere 14) . Briefly, 50 ng of coprostanol was added to 5 L of serum as an internal standard, and alkaline hydrolysis in 1 N ethanolic KOH and derivatization to the picolinyl esters were carried out 14) .…”
Section: Determination Of Sterol Concentrationsmentioning
confidence: 99%
“…Briefly, 50 ng of coprostanol was added to 5 L of serum as an internal standard, and alkaline hydrolysis in 1 N ethanolic KOH and derivatization to the picolinyl esters were carried out 14) . Then the picolinyl ester derivatives of the sterols were quantified by LC-MS/MS 15) .…”
Section: Determination Of Sterol Concentrationsmentioning
confidence: 99%